Pengembangan Game Edukasi Pengenalan Bahasa Inggris Dasar untuk Anak TK - Prima Ramadhayani Sandri; Anggy Trisnadoli; Erwin Setyo Nugroho (SMATIKA JURNAL : STIKI Informatika Jurnal, 2019)
The children have been introduced to English during they were in kindergarten. There are several ways that teachers can do with the students such as singing, drawing using media and doing some questions and answer. Language is the main tool for communicating in human life, both individually and social collectively. Student's language in the 4-6 years old is still not maximal, so parents and teachers play an important role in helping students to interact. Kindergarten students have started to be introduced to basic English, according to EPI (English Proficiency Index,) Indonesia is still ranked 51st out of 88 countries in the world in 2018. And it included in the low skill group. The way of learning is still using props as learning media. Therefore, technology is needed to help kindergarten students in learning basic English using 3D objects for their material. Based on the analysis of observations to kindergarten students was obtained an increase of 32.74%. In the analysis of the black box test results, it was found that all functions in the application can run smoothly according to the expected of the results. Furthermore, as the results of the analysis of interviews with kindergarten teacher stated that the game for the introduction of basic English is very helpful for the teaching and learning process.